2021
DOI: 10.1186/s12912-021-00597-0
|View full text |Cite
|
Sign up to set email alerts
|

Shared clinical decision-making experiences in nursing: a qualitative study

Abstract: Background Shared decision making (SDM) is a patient-centered nursing concept that emphasizes the autonomy of patients. SDM is a co-operative process that involves information exchange and communication between medical staff and patients for making treatment decisions. In this study, we explored the experiences of clinical nursing staff participating in SDM. Methods This study adopted a qualitative research design. Semistructured interviews were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
(46 reference statements)
0
12
0
1
Order By: Relevance
“…Lewis et al stated that nurses should be involved in the decision‐making process, given the increasing focus on inter‐professional collaboration and the role of nurses in coordinating the care of cardiac patients (Lewis et al, 2014). Chung et al also mentioned the important role of nurses in helping patients to understand their cardiac condition and treatment options (role of translator), by acting as a spokesperson for the patient towards patients' family and by acting as a communication bridge between the physician and the patient (Chung et al, 2021). It seems that the identified professional roles in cardiac surgery can be assigned to both the physicians and nurses, while their responsibilities and competence profiles in medical expertise differ.…”
Section: Discussionmentioning
confidence: 99%
“…Lewis et al stated that nurses should be involved in the decision‐making process, given the increasing focus on inter‐professional collaboration and the role of nurses in coordinating the care of cardiac patients (Lewis et al, 2014). Chung et al also mentioned the important role of nurses in helping patients to understand their cardiac condition and treatment options (role of translator), by acting as a spokesperson for the patient towards patients' family and by acting as a communication bridge between the physician and the patient (Chung et al, 2021). It seems that the identified professional roles in cardiac surgery can be assigned to both the physicians and nurses, while their responsibilities and competence profiles in medical expertise differ.…”
Section: Discussionmentioning
confidence: 99%
“…Decision coaching is effective in helping patients consider informed values and in guiding decision-making. In this way, nurses can work with patients and equip them with the knowledge and tools they need to make conscious and autonomous decisions about their own health [ 27 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the Italian literature includes articles on the importance of the topic [ 22 ] or reviews on the current situation [ 23 , 24 ], but there is no evidence on how healthcare professionals involve their patients in care processes and if there are differences between nurses and physicians. Indeed, most studies analyzed physicians’ and nurses’ approaches to SDM separately and focused on the healthcare professionals’ perspective rather than the point of view of the patient [ 25 , 26 , 27 , 28 ]. The only aspect that emerged concerned the area of patient information, highlighting the need for improved coordination and communication between nurses and physicians in order to provide information in a consistent and structured manner, thus reducing conflicting information for the patient [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The finding was echoed a previous study, that it is crucial for nurses learn the required attitudes of nursing through training as part of their socialization into the profession [ 30 ]. Additionally, as the nursing staff is familiar with the concept of SDM will agree and be willing to implement SDM [ 31 ]. Therefore, the present study showed that the SDMA score of the experimental group was better than that of the control group.…”
Section: Discussionmentioning
confidence: 99%